Analisis Faktor Yang Mempengaruhi Mahasiswa Dalam Pemilihan Model Jilbab (Studi Pada Mahasiswi Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga) - Shelyta, Ajeng; Hasib, Fatin Fadhilah (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims at determining the factor that influences on selecting the model of theirÂ headcovers, it is merely because the model of headcovers worn by the female students areÂ now vary. Therefore, there should be some factors that urges a female student as a consumerÂ to do a reasoned action on selecting the model of headcovers. This research is a quantitativeÂ research by using factor explanatory analysis. The characteristic of the population is theÂ students of Islamic Economy, FEB, Airlanga University which are wearing headcovers. The resultÂ of this research shows that from 18 factors gained from the data collection which thenÂ processed by factor analysis. The researcher found that there are 5 factors, i.e. Want to ShowÂ Identitiy, consumersâ environment, consumersâ comfort in dressing up, consumersâ society, andÂ consumersâ ease in dressing up.